2018
DOI: 10.1038/s41388-018-0126-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene activation of CEBPA using saRNA: preclinical studies of the first in human saRNA drug candidate for liver cancer

Abstract: Liver diseases is a growing epidemic worldwide. If unresolved, liver fibrosis develops and can lead to cirrhosis and clinical decompensation. Around 5% of cirrhotic liver diseased patients develop hepatocellular carcinoma (HCC), which in its advanced stages has limited therapeutic options and negative survival outcomes. CEPBA is a master regulator of hepatic function where its expression is known to be suppressed in many forms of liver disease including HCC. Injection of MTL-CEBPA, a small activating RNA oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 18 publications
5
51
0
Order By: Relevance
“…Searching for molecular mechanisms, we found that stabilization of key regulators of liver biology (C/EBPα, HNF4α, CUGBP1, Rb, and p53) under conditions of an HFD contributes to inhibition of steatosis. In agreement with this, several reports from Habib's group showed that the elevation of C/EBPα by a short‐activating RNA causes inhibition of liver cancer, metastasis, cirrhosis, fibrosis, and hepatosteatosis . In agreement with these observations, HFD‐treated GLKO mice and C/EBPα‐S193A mice have reduced C/EBPα and increased proliferation and spontaneously develop fibrosis and HCC, a situation observed in CUGBP1‐S302A mice.…”
Section: Discussionsupporting
confidence: 76%
“…Searching for molecular mechanisms, we found that stabilization of key regulators of liver biology (C/EBPα, HNF4α, CUGBP1, Rb, and p53) under conditions of an HFD contributes to inhibition of steatosis. In agreement with this, several reports from Habib's group showed that the elevation of C/EBPα by a short‐activating RNA causes inhibition of liver cancer, metastasis, cirrhosis, fibrosis, and hepatosteatosis . In agreement with these observations, HFD‐treated GLKO mice and C/EBPα‐S193A mice have reduced C/EBPα and increased proliferation and spontaneously develop fibrosis and HCC, a situation observed in CUGBP1‐S302A mice.…”
Section: Discussionsupporting
confidence: 76%
“…We calculated human-equivalent doses of 3 mg/kg MTL-CEBPA on the basis of individual animal weights. 22 In these conditions, the MTL-CEBPA administration via i.v. injection demonstrated the specific activation of its target C/EBPα mRNA and its downstream gene p21 ( Figures 4 B and 4C).…”
Section: Resultsmentioning
confidence: 99%
“… 17 , 20 , 21 Upregulation of C/EBPα activity has the potential to improve liver function and limit hepatocellular carcinoma (HCC) growth. 22 , 23 , 24 These findings demonstrated a critical role of C/EBPα expression in the regulation of cell motility, maturation, and tumorigenesis. 13 The role of C/EBPα expression in inflammation is not well characterized 25 although other CCAAT/EBPs such as C/EBPα have a clear role and are associated with activation of the NF-κB transcription factor.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations